PERSISTENCE POSITIVITY OF LACTATE DEHYDROGENASE RAPID DIAGNOSTIC TESTS ANTIGENS IN PREGNANT WOMEN AFTER ANTIMALARIA TREATMENT IN SOME HOSPITALS IN KATSINA - Eberemu, Nkiru C.; Usman, H. H.; Abasiryu, A. (FUDMA Journal of Sciences, 2024)
Malaria is a life-threatening disease caused by parasites transmitted to people through the bites of infected female Anopheles mosquitoes. It is preventable and curable. This study investigates the persistent positivity of Lactate Dehydrogenase (pLDH) Rapid diagnostic tests antigens in pregnant women after antimalarial treatment. The study was conducted in Turai Yaradua Maternity and Children’s Hospital Katsina and Federal Medical Centre Katsina. Samples were collected with the help of trained physicians. The result from this study shows that lactate dehydrogenase antigen persists in the blood after treatment with fensider (antimalaria drug). After administering the drug to the pregnant women found to be positive for malaria, it was observed that in all the age groups, day 3, day 7, and day 14 post-drug treatment were all still positive for malaria using the pLDH malaria rapid diagnostic tool. It was also observed that after 21 days post-treatment, all the different age groups were still positive for malaria except those aged 45 to 50 (95.0%). There is no statistically significant difference between the age of pregnancy p>0.05. The percentage positivity of pLDH started changing day 21 in 3rd trimester and the change peak at day 28 post-drug treatment in all three trimesters. There is no statistical significance difference between the age of pregnancy p>0.05. However, the first trimester shows the highest negative result (66.7%). It also shows that age, tribe, trimester of pregnancy, and occupation were statistically not associated with the persistence positivity of the pLDH. The parasite density might be responsible..